Divided Minds and Divine Judgement: - Harvey Cawdron (TheoLogica, 2023)
In this paper, I shall argue that Dissociative Identity Disorder (DID), a disorder in which seemingly independent identities (alters) arise within the same individual, can have considerable consequences in Christian theology. I shall focus on traditional Christian understandings of the afterlife. I shall begin by outlining DID, and shall argue that in some DID cases, alters appear to be different persons according to some definitions of personhood in Christian theology. I shall then illustrate the difficulty this raises for two influential ideas in the Christian tradition: the heaven and hell understanding of the afterlife, and the idea of the resurrection of the body. Finally, I shall consider some objections to the problem, and shall highlight which responses are the most plausible.